2015
DOI: 10.1074/jbc.m115.648550
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Proteolysis of the Membrane Protein YfgM by the FtsH Protease Depends on a Novel N-terminal Degron

Abstract: Background: YfgM is a membrane protein under regulatory control by FtsH. Results: Growth phase-dependent degradation of YfgM in Escherichia coli requires a novel N-terminal degron. YfgM interacts with the response regulator RcsB and acts as a negative regulator. Conclusion:The YfgM degron mediates degradation under stress conditions when the Rcs pathway is needed. Significance: The study reveals a new degron and provides insights into the function of YfgM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 80 publications
0
38
0
Order By: Relevance
“…For example, the FtsH and Lon substrate SoxS was shown to be stabilized tenfold by an N‐terminal His‐tag in comparison to the C‐terminally or untagged variant . In contrast, however, degradation of YfgM, which contains an N‐terminal degron, and several other FtsH substrates was not influenced by tags at the C‐ or N‐terminus . Due to the plasmid‐based expression system, the putative substrates are present at un‐physiological levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the FtsH and Lon substrate SoxS was shown to be stabilized tenfold by an N‐terminal His‐tag in comparison to the C‐terminally or untagged variant . In contrast, however, degradation of YfgM, which contains an N‐terminal degron, and several other FtsH substrates was not influenced by tags at the C‐ or N‐terminus . Due to the plasmid‐based expression system, the putative substrates are present at un‐physiological levels.…”
Section: Discussionmentioning
confidence: 99%
“…Degrons of FtsH substrates have been reported to lie in the C‐terminus (LpxC), N‐terminus (YfgM) or internally (RpoH) pointing out that different substrates are processed via different pathways [. Heterogeneous degrons are also known for other proteases.…”
Section: Discussionmentioning
confidence: 99%
“…ClpS), but such degron sequences are poorly understood in plastids (see Outstanding Questions). A recent study has identified a novel N-terminal degron for FtsH-driven proteolysis in bacteria (Bittner et al, 2015), raising the question of whether such a target recognition mechanism is conserved in chloroplasts. Meanwhile there have been several well-known examples of proteolytic regulation of specific chloroplast proteins.…”
Section: Proteolytic Remodeling Of the Photosynthetic Machineries In mentioning
confidence: 99%
“…Comprehensive substrate identification is necessary for determination of a common sequence signature or regulatory motif. Using substrate-trapping approaches, multiple substrates for Clp and FtsH proteases have been isolated in bacteria and in mammalian mitochondria Neher et al, 2003;Westphal et al, 2012;Bhat et al, 2013;Feng et al, 2013;Graham et al, 2013;Bittner et al, 2015). Trapping strategies use mutated, inactive forms of the protease or chaperone domains.…”
Section: Proteolytic Remodeling Of the Photosynthetic Machineries In mentioning
confidence: 99%
“…Accordingly, several membrane‐anchored substrates like FdoH, DadA, and YfgM were trapped with FtsH. A detailed analysis of YfgM revealed a novel N‐terminal degron and a function in the stress management in stationary growth phase …”
Section: Substrate Identification Of Aaa+ Proteases By Trapping Appromentioning
confidence: 99%